Avaliação do perfil de expressão gênica na lateralidade do câncer colorretal humano para um painel de marcadores e produção da proteína recombinante e anticorpos para tetraspanina co029 - Lucélia Antunes Coutinho Braga (2020)
The World Health Organization considers cancer to be an unquestionable public health problem. For Brazil, according to data from the Ministry of Health, it is estimated that 625 thousand new cases of cancer will occur in 2020, with colorectal cancer (CRC) being the second most common cancer for men and women. The latest GLBOCAN report identified CCR as the second most frequent cause of death among cancers. In the age of molecular medicine, the evaluation of gene expression of specific CCR markers, due to the heterogeneity of mutations, has become an important part of clinical trials and research. Among the different markers under study today, one potential is the tetraspanin protein CO029 (TspanCO029), responsible for the motility of the neoplastic cell. The epithelial-mesenchymal transition (EMT) markers E-cadherin and Vimentin, and the cell proliferation marker (Ki67) are worth mentioning. EMT is related to loss of cell differentiation, resistance to conventional treatments and the appearance of metastases. Ki67, on the other hand, is related to cell proliferation. Recent studies have shown that CRC laterality has prognostic and predictive values for response to specific treatments. Thus, the aim of the study was to evaluate the gene expression profile of the markers TspanCO029, E-cadherin, Vimentina and Ki67 in samples from patients with CRC of variable laterality and to produce the recombinant TspanCO029 and its antibodies. Gene expression data were correlated with patient and tumor characteristics. The results showed that there was a correlation between the gene expression of TspanCO029 with the EMT markers, and Ki67 in the positive samples of the right colon, while the group of patients aged 38 to 60 years showed greater expression for Ki67 and Vimentina. In addition, female patients showed greater expression of E-cadherin in the negative samples. The present study failed to define TspanCO029 as a risk prediction marker based on laterality, malignancy or lymph node metastasis, when isolated. However, when correlated to the other Ki67, E-cadherin and Vimentina markers, it was shown to be related to laterality. The recombinant protein as well as the antibodies were produced correctly and may be used in other works in the future.